Experimental measurement of preferences in health care using best-worst scaling (BWS): Theoretical and statistical issues - Axel C. Mühlbacher; Peter Zweifel; Anika Kaczynski; F. Reed Johnson (Health Economics Review, 2016)
For optimal solutions in health care, decision makers inevitably must evaluate trade-offs, which call for multiattribute valuation methods. Researchers have proposed using best-worst scaling (BWS) methods which seek to extract information from respondents by asking them to identify the best and worst items in each choice set. While a companion paper describes the different types of BWS, application and their advantages and downsides, this contribution expounds their relationships with microeconomic theory, which also have implications for statistical inference. This article devotes to the microeconomic foundations of preference measurement, also addressing issues such as scale invariance and scale heterogeneity. Furthermore the paper discusses the basics of preference measurement using rating, ranking and stated choice data in the light of the findings of the preceding section. Moreover the paper gives an introduction to the use of stated choice data and juxtaposes BWS with the microeconomic foundations.
Keywords: 330; Choice Experiments; Stated Preferences; Discrete Choice Experiments; Best-Worst Scaling; MaxDiff; Scaling